Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jac5.1221
|View full text |Cite
|
Sign up to set email alerts
|

Combating pharmacist burnout: A model for critical care clinical pharmacy faculty

Abstract: Burnout is a growing phenomenon among health care professionals in whom the prevalence has been estimated at greater than 50%. The adverse outcomes of burnout affect individuals, institutions, and patients. Although burnout literature in the profession of pharmacy is somewhat lacking, emerging data suggest a similar prevalence. Pharmacists who experience burnout typically suffer from emotional exhaus-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…Instead, lack of engagement only occurs in the presence of burnout. This is congruent with previous research that separately shows the positive relationship between anxiety and burnout (Koutsimani et al, 2019) and the relationship between burnout and unfavourable organisational consequences (Haase, 2020; Hagemann et al, 2020; Kaluzna et al, 2020; Salvagioni et al, 2017;Suñer-Soler et al, 2014). However, this article offers novel insight into the exact interplay between anxiety, burnout, and lack of engagement.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Instead, lack of engagement only occurs in the presence of burnout. This is congruent with previous research that separately shows the positive relationship between anxiety and burnout (Koutsimani et al, 2019) and the relationship between burnout and unfavourable organisational consequences (Haase, 2020; Hagemann et al, 2020; Kaluzna et al, 2020; Salvagioni et al, 2017;Suñer-Soler et al, 2014). However, this article offers novel insight into the exact interplay between anxiety, burnout, and lack of engagement.…”
Section: Discussionsupporting
confidence: 92%
“…This study supports previous literature that illustrates the negative implications of burnout (Haase, 2020; Hagemann et al, 2020; Kaluzna et al, 2020; Koutsimani et al, 2019; Salvagioni et al, 2017; Suñer-Soler et al, 2014). Specifically, this study finds that there is a sequential relationship between anxiety, burnout, and lack of engagement.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[8][9][10] Numerous studies have shown the prevalence of burnout among healthcare professionals, with estimates surpassing 50%. 11 Clinical and hospital pharmacists in the United States and other countries have reported alarmingly high burnout rates, that is, 53.2% 7 and 61.2%, 11 respectively. Interestingly, a study on burnout among U.S. clinical pharmacists reported over 61% of burnout despite 84% expressing satisfaction with their careers.…”
Section: Introductionmentioning
confidence: 99%